The critical turn : rhetoric and philosophy in postmodern discourse - Angus, Ian H.; Langsdorf, Lenore, 1943- (Carbondale : Southern Illinois University Press, 1993)
Concerned with criticizing representational theories of knowledge by developing alternative concepts of knowing and communicating, Ian Angus and Lenore Langsdorf bring together eight essays that are united by a common theme: the convergence of philosophy and rhetoric. In the first chapter, Angus and Langsdorf illustrate the centrality of critical reasoning to the nature of questioning itself, arguing that human inquiry has entered a "new situation" where "the convictions and orientations that have traditionally marked the separation of rhetoric and philosophy -- the concern for truth and the focus on persuasion -- have begun to converge on a new space that can be defined through the central term discourse." In these essays, this convergence of rhetoric and philosophy is addressed as it presents itself to a variety of interests that transcend the traditional boundaries of these fields. -- Publisher description.
Unsettled borders : envisioning critique at the postmodern site / Ian Angus and Lenore Langsdorf -- Words of others and sightings/citings/sitings of self / Lenore Langsdorf -- Critical rhetoric and the possibility of the subject / Raymie E. McKerrow -- Aristotle and Heidegger on emotion and rhetoric / Michael J. Hyde and Craig R. Smith -- Rhetoric, objectivism, and the doctrine of tolerance / James W. Hikins and Kenneth S. Zagacki -- Communication studies and philosophy / Calvin O. Schrag and David James Miller -- The algebra of history : Merleau-Ponty and Foucault on the rhetoric of the person / Richard L. Lanigan -- Learning to stop : a critique of general rhetoric / Ian Angus.
Chiefly papers presented at the annual meetings of the Speech Communication Association and the Society for Phenomenology and Existential Philosophy.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Rhetoric -- Congresses; Communication -- Philosophy -- Congresses; Rhétorique -- Congrès.; Information -- Philosophie -- Congrès.; LANGUAGE ARTS & DISCIPLINES -- Rhetoric; REFERENCE -- Writing Skills; LANGUAGE ARTS & DISCIPLINES -- Composition & Creative Writing; Communication -- Philosophy; Rhetoric; Rhetorik; Aufsatzsammlung; Postmoderne; Languages & Literatures; Philology & Linguistics; Conference papers and proceedings